2016
DOI: 10.12659/msm.901247
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions, Concentration of Endogenous Estradiol, Estrogen Receptor α (ERα) Polymorphism in Postmenopausal Women

Abstract: BackgroundThe goal of this study was to investigate the relationship between cognitive functions and the level of endogenous estradiol in postmenopausal women, according to which estrogen receptor α (ERα) polymorphism the woman carries.Material/MethodsThe study group consisted of 210 women. The inclusion criteria were: minimum 2 years after the last menstruation, FSH concentration 30 U/ml, and no dementia signs on Montreal Cognitive Assessment (MoCA). A computerized battery of Central Nervous System Vital Sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Cognitive sex biases suggest that sex hormones may play a role in brain development and functioning related to these cognitive domains. Accordantly, studies have shown that performance on verbal memory and processing speed tests worsen during the menopausal transition [ 73 , 74 ], depend on estrogen receptor genotype [ 75 ], and decline with increasing years since menopause [ 76 ]. In conjuction with these past findings, the specificity of our findings to cognitive domains with a female bias may further support a mechanistic role of the aromatization of androgens to estrogen in explaining our results.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive sex biases suggest that sex hormones may play a role in brain development and functioning related to these cognitive domains. Accordantly, studies have shown that performance on verbal memory and processing speed tests worsen during the menopausal transition [ 73 , 74 ], depend on estrogen receptor genotype [ 75 ], and decline with increasing years since menopause [ 76 ]. In conjuction with these past findings, the specificity of our findings to cognitive domains with a female bias may further support a mechanistic role of the aromatization of androgens to estrogen in explaining our results.…”
Section: Discussionmentioning
confidence: 99%
“…Lian reported that the AG Xba I and TC Pvu II genotypes were the most common among Europeans, while Dai found that the AA Xba I and TC Pvu II genotypes were the most common in Asians. Interestingly, both researchers reported that among both the white and Asian populations, the least common genotypes were GG Xba I and CC Pvu II [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that the regional distribution of estrogen receptors (ER) within the brain is surprisingly similar to the geography of brain pathology in Alzheimer’s disease [ 10 ]. The effect of Estrogen receptor alpha (ERα) polymorphisms on cognitive functions occurs due to the interaction of the concentration of estradiol with the receptor [ 11 , 12 ]. Thus, the estrogen/ER complex becomes an interesting candidate to discover the genetic background of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…These data are contrary to those found by [ 15 ], where the association was observed only in males [ 15 ]. However, the results for cognitive functions depends on which Xba1 polymorphism the woman carries [ 12 ].…”
Section: Discussionmentioning
confidence: 99%